The Effect Of Planting Media Composition And Npk Fertilizer Dosage On The Growth And Increasing Production Of Green Chili Plant (Capsicum annuum L.) - Nainggolan, Hotden Leonardo; Tampubolon, Yanto Raya (Agrotekma: Jurnal Agroteknologi dan Ilmu Pertanian, 2024)
Green chili is a large red chili that is harvested in its young phase and used for cooking ingredients. The need for chili continues to increase and the average consumption of large chili is 2.42 kg/capita/year and cayenne pepper is 2.19 kg/capita/year. The development of green chili in urban areas for household scale is constrained by limited land. The solution offered is to plant chili using planting media in polybags. This study aims to determine the composition of planting media, NPK fertilizer and their best interactions on the growth and production of green chili. The study used a Randomized Block Design (RAK) with 2 treatments, namely the composition of planting media (M) and NPK fertilizer (16-16-16) (P). The composition of the planting media was made into 4 levels, namely M0 (100% soil), M1 (50% soil + 50% rice husk charcoal), M2 (50% soil + 50% chicken manure) and M3 (50% soil + 25% rice husk charcoal + 25% manure). Each planting medium was weighed and the weight of M0 (10 kg/polybag), M1, M2 and M3 were 8 kg/polybag each. NPK fertilizer (16-16-16) was made into 4 levels, namely P0 (0 g/kg planting medium), P1 (0.112 g/kg planting medium), P2 (0.225 g/kg planting medium) and P3 (0.335 g/kg planting medium). NPK fertilizer was given together with dolomite base fertilizer 1.65 g/kg planting medium when mixing the planting medium until homogeneous and incubated for 21 days. The experiment was repeated 3 times, so that there were 16 experimental units each consisting of 3 polybags and a total of 144 polybags containing 1 (one) plant per polybag. The results obtained, the composition of the planting medium had a very significant effect on the stem diameter, a significant effect on the production of planting and per hectare but had no significant effect on plant height, number of branches and number of fruits. NPK fertilizer and its interaction with the composition of the planting media had no significant effect on all parameters. The best composition of the planting media was found in M3 and M2 which were not significantly different from each other in increasing the growth and production of green chili.